2019
DOI: 10.1155/2019/3940397
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Cultivated Plants in Kaišiadorys District, Lithuania: Possible Trends for New Herbal Based Medicines

Abstract: Background. Despite the growing body of ethnobotanical studies in Europe, publications are scarce in Lithuania. Ethnobotanical study in Kaišiadorys district is one of the few from this field done in Lithuania. Lithuania is divided into five ethnographic regions, and Kaišiadorys district is an area which borders with the three of them (Aukštaitija, Dzūkija, and Suvalkija), which determines the ethnographic distinctiveness of the area. The aim of this study was to determine the occurrence of cultivated medicinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…Rowanberries are recommended in folk medicine to treat hemorrhoids, hypertension (Kültür 2007;Polat and Satıl 2012), respiratory tract infections, rheumatism and gout (Vogl et al 2013). In Lithuania (Kaišiadorys dictrict) preparations from rowanberries were administered orally in constipation and cough, whereas bark decoction was used as a wound wash (Pranskuniene et al 2019). Sak et al (2014) revealed that a tea prepared from bark of S. aucuparia has been used in Estonia to treat cancer diseases.…”
Section: Europementioning
confidence: 99%
See 1 more Smart Citation
“…Rowanberries are recommended in folk medicine to treat hemorrhoids, hypertension (Kültür 2007;Polat and Satıl 2012), respiratory tract infections, rheumatism and gout (Vogl et al 2013). In Lithuania (Kaišiadorys dictrict) preparations from rowanberries were administered orally in constipation and cough, whereas bark decoction was used as a wound wash (Pranskuniene et al 2019). Sak et al (2014) revealed that a tea prepared from bark of S. aucuparia has been used in Estonia to treat cancer diseases.…”
Section: Europementioning
confidence: 99%
“…They are often consumed raw or processed into jams, wines etc. (Tardío et al 2006;Kalle and Sõukand 2012;Łuczaj et al 2013;Pranskuniene et al 2019). Fruits of S. aucuparia, S. intermedia and S. rupicola are bread ingredients in Estonia (Kalle and Sõukand 2012).…”
Section: Food Usementioning
confidence: 99%
“…E são muitas vezes usadas somente em sintomas, como tosse, dores de garganta, inflamação e inchaço da mucosa nasal durante um resfriado. As formas de preparo mais empregadas são os chás e inalação (Pranskuniene et al, 2019).…”
Section: A Fitoterapia Como Alternativa Terapêutica Nas Doenças Respiunclassified
“…The use of P. padus bark was mentioned ten times more often than the use of fruits and eight times more often than the use of flowers. The symptoms and uses mentioned in other studies are the same as those mentioned in the Latvian records: the fruits were used to treat diarrhoea and the flowers were used for joint and rheumatic pain and for treating erysipelas(Kujawska et al, 2017;Pranskuniene et al, 2019;Sõukand et al, 2017). In addition, the use of P. padus was also reported in the records of Latvian folk medicine for treating disorders such as headaches, toothaches, pain in the ears, neck and stomach, coughs, bruises, and swelling.…”
mentioning
confidence: 80%
“…padus has been commonly reported(Kujawska et al, 2017;Pranskuniene et al, 2019;Sõukand et al, 2017). However, in the records of Latvian folk medicine, the bark was the most frequently mentioned part of the plant.…”
mentioning
confidence: 99%